IMPLEMENTASI KEBIJAKAN PERLINDUNGAN DAN PEMENUHAN HAK PENYANDANG DISABILITAS DI DINAS SOSIAL SIDENRENG RAPPANG : IMPLEMENTASI KEBIJAKAN PERLINDUNGAN DAN PEMENUHAN HAK PENYANDANG DISABILITAS DI DINAS SOSIAL SIDENRENG RAPPANG - Samil Samil; Nurjannah Nonci; Irwan Irwan (LPPM Universitas Abdurrab, 2026)
This study aims to analyze the implementation of local government policies related to the protection and fulfillment of the rights of persons with disabilities in Sidenreng Rappang Regency, particularly through the Social Affairs Office. This research employs a qualitative approach using field research methods. Data were collected through observation, interviews, and documentation studies.The results indicate that the implementation of the policy through Sidenreng Rappang Regency Regional Regulation Number 6 of 2023 concerning the protection and fulfillment of the rights of persons with disabilities has been carried out quite effectively. This is reflected in effective and open communication between the government and the disability community, enabling them to better understand their rights. The officials of the Social Affairs Office have fulfilled their responsibilities by conducting socialization of the regional regulation and providing adequate platforms and facilities for persons with disabilities. Furthermore, the policy implementation has adhered to standard operating procedures (SOPs), which serve as guidelines for implementers to carry out the policy accurately and systematically.